Finding the Reaction Constant Between Humic Acid and Metal Ions by Fluorescence Quenching Effect - Po Cheng, Wen; Tsang Lu, Yi; Fang Yu, Ruey; Ru Lin, Xin; Xin Li, Han (International Journal of Engineering and Technology, 2018)
Humic acid was used as the removal target for evaluating the coagulation efficiency in this study. When the metal ions mix with humic acid solution, a Fluorescence quenching effect may be observed conditionally. This effect can be described by Stern-Volmer linear equation which can be used for quantifying the quenching constant (KQ) of the Fluorescence quenching effect. In addition, the result of the quenching constant (KQ) was used to explain the electron-neutralization capability of the metal ions at different pH. The results indicated that there is no significant Fluorescence quenching effect between the additions of monovalent Na+ ion, divalent Ca2+ and humic acid. Otherwise, when pH of the FeCl3 solution was between 4.5 and 5.5, fluorescence quenching effect obviously occurred. The maximum KQ value was found to be 305,990 at pH 5. It means that the higher KQ value is, the better complex reaction between humic acid and aluminum salts will be. Through the KQ value study, the optimum pH can be quantified when humic acid solution is reacted with ferric ion.Â